The Effects of Transformational and Transactional Leadership Style on Job Satisfaction - Kamelia Mohamed Saber; Wafaa Hasan Mostafa (Journal of High Institute of Public Health, 2009)
Effective leadership plays an important role in the growth and better performance of the organization. Understanding factors that influence job satisfaction is keys to enhancing morale within the profession and creating a secure future to support the demands of the aging population. Nurse’ managers are in an outstanding position to influence job satisfaction of nurses. By examining the relationship of perceived leadership styles of nurse managers and job satisfaction of staff nurses, the nursing profession can begin to establish positive, mutually beneficial relationships leading to efficiency, productivity, and job satisfaction for all nurses. This study was conducted in Alexandria University Students’ Hospital to determine head nurses’ leadership style as perceived by staff nurses and its relationship to nurses’ job satisfaction. A total of 120 staff nurses (n=120) working in all inpatient unit were chosen and data was collected using two questionnaires; the Multifactor Leadership Questionnaire (M.L.Q) and Job Satisfaction Questionnaire. The results revealed significant difference between head nurses' leadership style and nurses job satisfaction. Nurses who perceived head nurses as transformational leaders (TF) were more satisfied with intrinsic factors than nurses who perceived head nurses as transactional leaders (TA), who were satisfied more with extrinsic factors. In relation to intrinsic job satisfaction factors, nurses who perceived head nurses as TF leaders revealed with recognition for achievement, the work itself & responsibility and work hours, but for extrinsic job satisfaction factors serealed with supervision and job security. On the other hand, nurses who perceived head nurses as TA leaders were satisfied with intrinsic factors as sense of achievement, except the work itself & responsibility and for extrinsic factor they were Satisfied with Interpersonal relationship. No significant difference was found between their demographic characteristics except nurses’ age among nurses who perceived head nurses as transactional leaders. Managerial implications are presented based upon these results.